(untitled) (Research, Society and Development, 2022)
The Caatinga, of Brazilian exclusivity, is compound by adapted plants for the climate-specific conditions present in this region. The natural resources in this phytogeography domain are used for local communities as foods source, regional economics develops, and traditional medicine. Folk medicine is applied as a local tradition through the fraction of the plants, such as roots, leaves, and fruits, to treat inflammation, tumor, metabolic or degenerative diseases. Although the technological pharmaceutical industrial process shows exponential development in benefits for human health, the search for new treatments, naturals, and alternatives linked with the significant consciousness of the populations some knowledge about folk medicine and their natural compounds are not vast. In this way, the present review aimed to realize the systematic research considering 26 species endemics in Caatinga and their most significant biological potential. As a result, it was observed that have more studies with the antioxidative and immunomodulatory activities. The previous knowledge shows the relation between the accumulation of reactive oxygen species (ROS) and the development of different immunological diseases. With this review, we propose to contribute to the biotechnological potential of the Caatinga for science health.